Forgotten Poles in the history of neurology: from Flatau to Frey - Gotowiec, Mateusz (Arquivos de Neuro-Psiquiatria, 2022)
With the majority of eponyms being removed from disease classification systems, it is even more difficult to remember the neurologists who influenced the development of techniques and understanding of the brain over the last centuries. Determining whether Polish researchers were given similar attention to Western equivalents based on eponymic presence in medical databases is an interesting way to provide an overview of unremembered Polish neurologists. This work aims to recognize the developments of forgotten Polish neurologists, whose work, although important, was not properly appreciated over the centuries.
Keywords: History, 19th Century; History, 20th Century; History of Medicine; Neurology